Adult height in Turkish patients with Turner syndrome without growth hormone treatment - (:unkn) unknown (TURKISH J PEDIATRICS, 2008)
Spontaneous adult height (AH) in Turner syndrome (TS) varies among populations. Population-specific AH data is essential to assess the efficacy of growth-promoting therapies in TS. A multicenter study was performed to establish AH of non-growth hormone (GH)-treated Turkish patients with TS. One hundred ten patients with TS (diagnosed by karyotype) who reached AH (no growth in the previous year, or bone age > 15 years) without receiving GH treatment were included in the study. The average AH was found to be 141.6 +/- 7.0 cm at the age of 22.9 +/- 6.2 years, which is 18.4 cm below the population average and 16.4 cm below the patients' mid-parental heights. Bone age at start of estrogen replacement was 12.3 +/- 1.3 year. Karyotype distribution of the patients was 45X (43%), 4SX/46XX (16%), 4SX/46xi (12%), 45XiXq (10%) and others (19%). When the patients were evaluated according to their karyotype as 45X and non-45X, no significant difference in AH was observed (142.4 +/- 6.9 cm vs 140.9 +/- 7.1 cm, respectively). Adult height of non-GH-treated Turkish TS patients obtained in this study was comparable to that of other Mediterranean populations, but shorter than that of Northern European patients. Karyotype does not seem to affect AH in TS.
Keywords: Turner syndrome; final height; adult height; karyotype; growth; growth hormone; FINAL HEIGHT; GIRLS; KARYOTYPE